ANALISIS PERLINDUNGAN HUKUM HAK ATAS MEREK DALAM PUTUSAN MAHKAMAH AGUNG NOMOR 1349 K/Pdt.Sus-HKI/2022 - Satriatama, Danindra Lazuardi; Afwa, Ulil (Lembaga Penelitian Pengabdian Masyarakat dan Pusat Kajian - Universitas Ngurah Rai, 2024)
This study aims to analyze the legal protection of Trademark rights under Law Number 20 of 2016 on Trademarks and Geographical Indications within the context of Supreme Court Decision Number 1349 K/Pdt.Sus-HKI/2022. This research employs a normative juridical research methodology with a case approach and analytical descriptive research specifications. Secondary data sources encompass primary, secondary, and tertiary legal materials. Data collection for this research utilizes library research methods, subsequently presented in the form of narrative texts, employing qualitative normative methods as a data analysis approach. Based on the discussions, it can be concluded that the Plaintiff, as the owner of the ERG Trademark, received limited legal protection for their Trademark rights in Supreme Court Decision Number 1349 K/Pdt.Sus-HKI/2022, which does not align with the provisions of Law Number 20 of 2016 on Trademarks and Geographical Indications